Are the Economically Poor Information Poor? Does the Digital Divide Affect the Homeless and Access to Information? - Hersberger, Julia A (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Homeless persons lack economic capital, but it is less clear whether they concomitantly lack important information capital. The basic information needed by the homeless is not available on the Internet as this is information controlled by governmental social services agencies. But does this result in a state of information poverty? This paper examines the issues of how the lack of access. . .